2014
DOI: 10.1155/2014/813120
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten Oxide and Polyaniline Composite Fabricated by Surfactant‐Templated Electrodeposition and Its Use in Supercapacitors

Abstract: Composite nanostructures of tungsten oxide and polyaniline (PANI) were fabricated on carbon electrode by electrocodeposition using sodium dodecylbenzene sulfonate (SDBS) as the template. The morphology of the composite can be controlled by changing SDBS surfactant and aniline monomer concentrations in solution. With increasing concentration of aniline in surfactant solution, the morphological change from nanoparticles to nanofibers was observed. The nanostructured WO3/PANI composite exhibited enhanced capaciti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
(52 reference statements)
1
12
0
Order By: Relevance
“…However, the value of the areal capacitance obtained is a lot of improvement from 4 mF cm −2 obtained by Nwanya et al at a scan rate of 50 mV s −1 (Nwanya et al 2014). It is also comparable to 25 mF cm −2 obtained by Zou et al (Zou et al 2014) for a composite of WO 3 and polyaniline at a scan rate of 5 mV s −1 . The frequency response to the mechanism of the charge storage were further studied using electrochemical impedance spectroscopy (EIS) within the frequency range of 0.01 Hz to100 kHz at a voltage amplitude of 10 mV.…”
Section: Electrochemical Studysupporting
confidence: 81%
“…However, the value of the areal capacitance obtained is a lot of improvement from 4 mF cm −2 obtained by Nwanya et al at a scan rate of 50 mV s −1 (Nwanya et al 2014). It is also comparable to 25 mF cm −2 obtained by Zou et al (Zou et al 2014) for a composite of WO 3 and polyaniline at a scan rate of 5 mV s −1 . The frequency response to the mechanism of the charge storage were further studied using electrochemical impedance spectroscopy (EIS) within the frequency range of 0.01 Hz to100 kHz at a voltage amplitude of 10 mV.…”
Section: Electrochemical Studysupporting
confidence: 81%
“…Electro‐co‐deposition of tungsten oxide (WO 3 ) and PAni with carbon electrode and sodium dodecylbenzene sulfonate (SDBS) surfactant as the template was performed. This nanostructured PAni/WO 3 composite has shown a capacitance of 201 Fg −1 at 1.28 mAcm −2 in large potential window with 78% retention of capacitance . Earlier, Sopčić et al had observed that PAni/RuO 2 composites with binder poly(vinylidene fluoride) (PVdF) display an electrochemical capacitance of 526 Fg −1 .…”
Section: Application Of Polyaniline In the Field Of Supercapacitorsmentioning
confidence: 92%
“…The interest in utilizing transition metal oxide films is due to its pseudocapacitive character related to chemisorption processes and redox reactions that take place at the surface [80]. Since nanostructured WO 3 has already proved to enhance capacitive performances due to its large surface area and low charge transport resistance [52], it was used for neural recordings applications [69]. The optimization of the electrodeposition parameters led to a slight increase on the charge storage capacity (∼10%) and a decrease of the impedance values, of approximately 40% ( Fig.…”
Section: Neural Electrodesmentioning
confidence: 99%